Feasibility of Academic Blogs as Learning Media for Electromagnetik Induction Material - Angraeni, Lia; Sari, Ira Nofita; Junghin, Noryi; Matsun, Matsun (Kappa Journal, 2023)
Based on pre-observation results, researchers found that student learning outcomes in electromagnetic induction material were still below the standards set by the school. This is due to the lack of learning media used. Therefore, it is necessary to develop innovative media that can support learning, namely blog-based learning media. This research aims to determine feasibility according to media experts, feasibility according to material experts, and test students' responses to the media being developed. This research uses Thiagarajan's R&D steps with a 4D model, namely (Define, Design, Develop, and Disseminate), but in its implementation in this research it is modified to 3D, namely Define, Design, and Develop. The results of data analysis show that from the media aspect it is categorized as very appropriate with a score of 91%, from the material aspect it is categorized as appropriate with a score of 75% and the results of student responses to the media being developed are categorized as very feasible with a score of 95%. Based on this, it can be concluded that the learning media with the Academic Blog is said to be suitable for use in learning electromagnetic induction material.